Emerging roles of macrophages in heart failure and associated treatment approaches - Lan Xie; Jinyong Chen; Yidong Wang; Chengjiang Jin; Yao Xie; Hong Ma; Meixiang Xiang (SAGE Publishing, 2023)
Heart failure is typically caused by different cardiovascular conditions and has a poor prognosis. Despite the advances in treatment in recent decades, heart failure has remained a major cause of morbidity and mortality worldwide. As revealed by in vivo and in vitro experiments, inflammation plays a crucial role in adverse cardiac remodeling, ultimately leading to heart failure. Macrophages are central to the innate immune system, and they are the most indispensable cell type for all cardiac injuries and remodeling stages. The immediate microenvironment regulates their polarization and secretion. In this review, we summarize the phenotypic heterogeneity and governing roles of macrophages in the infarcted, inflamed, and aging heart and assess their significance as potential therapeutic targets in heart failure. We also highlight the current missing links and major challenges in the field that remain to be addressed before macrophages can be exploited for therapeutic applications.